Using 3D motion capture to analyse ice hockey shooting technique on ice - Swarén, M.; Söhnlein, Q.; Stöggl, T.; Björklund, G. (Proceedings of the 7th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2019)
This study investigates the feasibility to use a passive marker motion capture system on ice to collect 3D kinematics of slap shots and one timers. Kinematic data were collected within a volume of 40x15x2 m by 20 motion capture cameras at 300 Hz, a resolution of 12 megapixels and a mean residual for all cameras of 3.4±2.5 mm, at a distance of 11.6 m. Puck velocity, blade velocity, ice contact time and distance to the puck were analysed for ten consecutive shots for each technique, for two professional ice hockey players. The total mean puck velocity was 38.0 ± 2.7 m/s vs. 36.4 ± 1.0 m/s. (p=0.053), for one timers and slap shots respectively. One player had higher puck velocity with one timers compared to slap shots 40.5 ± 1.0 m/s vs. 36.9 ± 1.0 m/s (p=0.001). Puck contact time was longer for slap shots than for one timers, 0.020 ± 0.002 s vs. 0.015 ± 0.002 s, (p<0.001). The motion capture system allowed continuous kinematic analyses of the puck and blade velocities, ice contact times and detailed stance information. The results demonstrate the possibilities to use motion capture systems to collect and analyse shooting kinematics on ice, in detail.